Nutritional Status Correlated with the Development of Toddlers Aged 24-60 Months - Maria Ulfa; Laily Prima Monica; Wahyu Wibisono; Ulfa Husnul Fata (STIKes Patria Husada Blitar, 2023)
Nutritional status is one of the physical variables that affects a child's growth and development. Considering that children are still in the process of growing and developing, it is crucial that their nutritional demands are addressed to the fullest extent possible. The purpose of this study was to determine how nutritional status and the development of toddlers aged 24 and 60 months related one another. Cross-sectional study was employed as the methodology of the study. 20 toddlers was served as the sample, which was collected through complete sampling at the Posyandu in Kuningan Village, Kanigoro District, and Blitar Regency. The Spearman Rank correlation test was used to examine the data. The study's findings indicated a correlation between nutritional status and toddlers' development aged of 24 and 60 months. Good category of nutritional status of the Toddlers showed good development results appropriate to their age. The recommendation of this research is for parents to pay more attention to nutritional intake and provide stimulation according to their toddler's development so that disorder in the developmental stage will not be occurred.